EVALUASI DAN DESAIN ULANG TOILET BANTUAN PEMERINTAH BERBASIS SNI DI DESA PENEBAL, KABUPATEN BENGKALIS - Asril, Syamsul; Syarimah, Marita; Aminah, Hamidatul (Yayasan Nusantara Hasana Berdikari, 2026)
The household toilet assistance program is one of the local government’s efforts to improve access to adequate sanitation in rural areas. In 2025, the Bengkalis Regency Government implemented a toilet assistance program in several villages, including Penebal Village. This study aims to evaluate the technical compliance of government-assisted toilets in Penebal Village with Indonesian National Standard (SNI) 2398:2017 and to formulate recommendations for septic tank redesign based on the applicable standard. The study employed a descriptive–evaluative method through field observations of the standardized toilet type constructed under the assistance program. Evaluation parameters included toilet floor and wall conditions, type of toilet fixture, air ventilation, septic tank dimensions and materials, gas ventilation system, wastewater infiltration system, and the distance between septic tanks and clean water sources. The observed conditions were then compared with the technical requirements stipulated in SNI 2398:2017 and related sanitation regulations. The results indicate that several components of the government-assisted toilets comply with the technical standards, such as the use of water-seal toilets, septic tank compartmentation, and watertight construction materials. However, non-compliance was identified in floor and wall impermeability, ventilation systems, septic tank dimensions, and the absence of standard-compliant wastewater infiltration systems. Based on these findings, improvements through a septic tank redesign in accordance with SNI 2398:2017 are recommended to ensure optimal and sustainable sanitation system performance.